Marketing and Strategy in India: Adapting to a Diverse and Evolving Market Environment - Wahid, A Mohamed (Journal of Global Economy, Business and Finance, 2025)
India's vast and diverse consumer base presents unique challenges and opportunities for marketers. With a growing middle class, increasing digital adoption, and highly varied regional preferences, brands must develop dynamic marketing strategies to succeed in this complex marketplace. This paper explores how businesses in India can adapt their marketing strategies to effectively target diverse audiences, leverage digital platforms, and differentiate their products. The study examines the impact of cultural diversity, the role of innovation in product positioning, and the growing importance of social media and influencer marketing. Additionally, it outlines key strategic considerations for brands to navigate regulatory challenges, economic shifts, and changing consumer behavior.